Philosophy of Education and History of Philosophy: Transformation of the Dialogue between Educators and Philosophers in the 21st Century - O. A. Vlasova (Высшее образование в России)
The paper examines the problem of transformation of the dialogue between educators and philosophers (within the framework of the scientific dialogue between the philosophy of education and the history of philosophy) in the 21st century. The work implements a perspectivist approach, exploring the interdisciplinary field of philosophy of education and history of philosophy from the position of an actor of science in measuring the dialogue between educators and philosophers. Monographs and scientific papers of 1990–2021 serve as a source material for the study. In the course of the study, the author’s approach to the study of the current state and discussions of the philosophy of education in the perspective of the dialogue between teachers and historians of philosophy has been substantiated. The article generalizes the features of the transformation of the field of philosophy of education in 1990–2021, identifies the periods of change in the dialogue between the philosophy of education and the history of philosophy, highlights the general directions of modern discussions. It is demonstrated that in modern research the dialogue between educators and historians of philosophy occurs at all levels of philosophy of education: the level of methodology; practical developments of thinkers of the past; cultural, social, value context. At the same time, the role of the historian of philosophy is to deepen criticism and interpretation of the pedagogical discourse of the past in response to a specific request from specialist educators, in clarifying certain aspects of philosophy and contextualizing them within the framework of the situation of education. The article shows the importance of studying the historical and philosophical layer of modern problems, indicates the continuing relevance of the study of the philosophy of the past and the work of the historian of philosophy for specialists in various branches of the humanities.